Python for Teenagers : Learn to Program like a Superhero! - Payne, James R.; SpringerLink (Online service); O'Reilly (Firm); Serials Solutions (New York : Apress, 2022)
Discover everything you need to learn Python programming, with fun examples along the way. This book gives you ideas for how to turn your love of programming into a job you'll love. Start with the basics and before you know it, you'll be building your own web sites, doing white-hat hacking, finding code bugs and errors, and creating games, including using Python to roll characters for RPGs. Every chapter is relaxed and informal, like learning with a cool teacher all the time. Computers, phones and the web are your playground, and you'll be ready to join the party with your own content. Going beyond posts and uploads means learning to program, and Python is a great choice to get started. It's quick to learn, it's flexible, and if you want, it may get you a Python job that pays more than minimum wage when you're out of school. Python for Teenagers is the most fun you'll have while learning.
1. Introduction to Computer Programming and Python -- 2. It All Adds Up -- 3. String Things Along -- 4. Making Decisions -- 5. Loops and Logic -- 6. Using What We've Learned -- 7. Saving Time with Functions, Modules, and Built-ins -- 8. Using Classes and Objects -- 9. Network Programming with Python -- 10. Python Frameworks -- 11. Python for Gaming -- 12. Hacking (Ethical) and Cryptography -- 13. Extending Python -- 14. Your Python Career.
Mode of access: World Wide Web.
Keywords: Making decision; Loops and logic; Using classes and objects; Electronic books